Analisis Dan Evaluasi Kurikulum Program Studi Pendidikan Seni Rupa Pada Perguruan Tinggi: Tinjauan Komprehensif Tataran Teoretis Dan Implementasi Dalam Konteks Merdeka Belajar Kampus Merdeka - Ega Harna B; Ambiyar; Fahmi Rizal (Kilau Publishing, 2026)
Higher art education in Indonesia is currently at a crucial crossroad that demands constant adaptation to the dynamics of the times. Reorienting the curriculum is no longer just an administrative choice but an existential imperative for higher education institutions to remain relevant in producing competent art educators and practitioners in the era of digital disruption. This article aims to conduct a comprehensive analysis and evaluation of the Fine Arts Education study program curriculum, both at the theoretical level and in its practical implementation within the context of Merdeka Belajar Kampus Merdeka (MBKM). The research method used is library research with a qualitative-descriptive approach through the CIPP (Context, Input, Process, Product) evaluation model. Theoretical analysis shows that the curriculum is built on a strong philosophical foundation, integrating local wisdom with a competitive global orientation. However, at the implementation level, significant gaps exist, such as technical and administrative obstacles in MBKM implementation, including SKS conversion issues, disparities in digital infrastructure, and a lack of technical understanding among the academic community regarding the new policies. The article concludes with strategic recommendations, including flexibility-based curriculum reorientation, enhancing the digital competence of lecturers, and strengthening external partnership networks to ensure the quality of fine arts education is superior and sustainable in Indonesia